Soviet perspectives on international relations 1956-1967 - by William Zimmerman. (Princeton University Press, 1969)
"Sponsored by Institute of War and Peace Studies and Russian Institute." Introduction -- The emergence of international relations as a discipline -- The actors -- The hierarchy -- The distribution of power -- United States foreign policy from the Soviet perspective -- The balance of power as system and policy -- Post-imperialism and the transformation of Soviet foreign policy.